Conceptual design of sub-exa-watt system by using optical parametric chirped pulse amplification. (March 2016) - Kawanaka, J.; Tsubakimoto, K.; Yoshida, H.; Fujioka, K.; Fujimoto, Y.; Tokita, S.; Jitsuno, T.; Miyanaga, N.
Abstract: A 50 PW ultrahigh-peak-power laser has been conceptually designed, which is based on optical parametric chirped pulse amplification (OPCPA). A 250 J DPSSL and a flash- lamp-pumped kJ laser are adopted as new repeatable pump source. The existed LFEX-laser with more than ten kilo joules are used in the final amplifier stage and the OPCPA with the 2x2 tiled pump beams in random phase has been proposed with several ten centimeter aperture. A pulse duration of amplified pulses is set at less than 10 fs. A broadband OPCPA with ∼500 nm of the gain spectral width near 1 μm is required. A partially deuterated KDP (p-DKDP) crystal is one of the most promising nonlinear crystals and our numerical calculation ensured such ultra-broad gain width. p-DKDP crystals with several deuteration ratio have been successfully grown.